Changes Of Symptoms And The Ability Of Anxiety Patients After Exercise Of Thought Stopping And Family Psychoeducation - Laela, Sri; Mustikasari, Mustikasari; Wardani, Ice Yulia (Universitas Muhammadiyah Semarang, 2018)
Patients with degenerative disease were hospitalized may experience an anxiety psychological problem affecting the condition of the illness. The handling of this case aims to determine the change of symptom signs and ability of anxiety patients after exercise thought stopping and family psychoeducation. The design was case study with 25 participants. The analysis was performed on symptoms and abilities of patients and families before and after nursing intervention, thought stopping and family psychoeducation. The case handling on the same topic has been done before, but that distinguishes the author using Peplau's interpersonal theory approach. This makes its different and important to do. The result of the case handling shows the age of 18-60 years, female 13 people, men 12 people, Sundanese and Â the decreased signs of anxiety symptoms, also the increased the ability of families in caring for family members who experienced anxiety. Nursing intervention, thought stopping and family psychoeducation are recommended as nursing therapy for patients anxiety with degenerative diseases.